Blue-collar Broadway : the craft and industry of American theater - White, Timothy R. (University of Pennsylvania Press, 2015)
A rich history of American theater, Timothy White's Blue-Collar Broadway tells the story of the people who created costumes, shoes, scenery, lights, and props. From the 1880s to the 1990s, White explores the shifting centers of theatrical craft and their impact on the nation and the iconic New York City district of Times Square.